2007
DOI: 10.1002/ijc.22514
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti‐inflammatory drugs and risk of lung cancer

Abstract: Regular aspirin and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) use is associated with a reduced risk of colorectal cancer. The effect of NSAIDs on the risk of other cancers remains unclear. To evaluate whether use of aspirin or other specific NSAIDs protects against lung cancer, we conducted a case-control study nested in a cohort of subjects 40-84 years old in 1995-2004, without a diagnosis of cancer before the study start date, and with at least 2 years of enrollment with a general practitioner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 32 publications
3
46
2
Order By: Relevance
“…Fewer studies observed an increased risk of lung cancer for aspirin users. The only one with a significant result was a nested case-control study using the UK Health Improvement Network database in which a 53% increased risk of lung cancer was reported for men and women who received prescriptions for 150 mg or more per day of aspirin for at least 1 year (Hernandez-Diaz and Rodriguez, 2007). This increased risk is similar to what we observed for high quantity aspirin users in our cohort but the aspirin intake on which it was based is much lower.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Fewer studies observed an increased risk of lung cancer for aspirin users. The only one with a significant result was a nested case-control study using the UK Health Improvement Network database in which a 53% increased risk of lung cancer was reported for men and women who received prescriptions for 150 mg or more per day of aspirin for at least 1 year (Hernandez-Diaz and Rodriguez, 2007). This increased risk is similar to what we observed for high quantity aspirin users in our cohort but the aspirin intake on which it was based is much lower.…”
Section: Resultssupporting
confidence: 82%
“…For lung cancer, several meta-analyses with different coverage of published results have offered varying results and interpretations. Of the two that focused solely on lung cancer, aspirin users were found to have a significant 27% lower risk in one (Khuder et al, 2005) and a nonsignificant 9% lower risk in the other (Hernandez-Diaz and Rodriguez, 2007). In two other meta-analyses in which lung cancer was embedded in a wider review of many cancers, the first reported a 16% lower risk for aspirin users that was compatible with no effect or a slightly reduced risk (Gonzalez-Perez et al, 2003), and the other, limited to cohort studies, reported no association (Bosetti et al, 2006).…”
mentioning
confidence: 99%
“…20 The use of NSAIDs was also linked to the protective effects against cancers in other sites such as breast, esophagus, stomach, lung, prostate and ovary. [21][22][23][24][25][26][27][28][29] However, the results for these cancer types are less consistent compared to those for colorectal cancer.…”
Section: Nsaids and Cancer Chemopreventionmentioning
confidence: 99%
“…Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) used in relation to lung cancer have been investigated in at least 20 studies, including four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003), fourteen cohort studies (Paganini-Hill et al, 1989;Thun et al, 1993;Schreinemachers and Everson, 1994;Langman et al, 2000;Akhmedkhanov et al, 2002;Friis et al, 2003;Holick et al, 2003;Sørensen et al, 2003;Ratnasinghe et al, 2004;Skriver et al, 2005;Hayes et al, 2006;Hernández-Diaz and Rodriguez, 2007;Jacobs et al, 2007;Wall et al, 2007) and three randomised trials (Peto et al, 1988;Lee et al, 1995;Cook et al, 2007). Significantly decreased risks were observed in three of the four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002), although all were based on selfreported drug use after diagnosis of cancer, raising the possibility of recall bias.…”
mentioning
confidence: 99%
“…Significantly decreased risks were observed in three of the four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002), although all were based on selfreported drug use after diagnosis of cancer, raising the possibility of recall bias. Of the remaining studies in which drug details were obtained before diagnosis, only three found significant inverse associations, two (but with overlapping data) with regular aspirin use (Schreinemachers and Everson, 1994;Ratnasinghe et al, 2004) and a third with other NSAID use (Hernández-Diaz and Rodriguez, 2007). The remaining studies, including the three low-dose aspirin randomised trials (Peto et al, 1988;Lee et al, 1995;Cook et al, 2007) and a Danish cohort study that we previously reported (Skriver et al, 2005), revealed a modest, nonsignificantly decreased risk, no appreciable effect or an increased risk, respectively.…”
mentioning
confidence: 99%